Effects of leachates from UV-weathered microplastic on the microalgae Scenedesmus vacuolatus - Rummel, Christoph D.; Schäfer, Hannah; Jahnke, Annika; Arp, Hans Peter H.; Schmitt-Jansen, Mechthild (Analytical and bioanalytical chemistry, 2022)
Plastics undergo successive fragmentation and chemical leaching steps in the environment due to weathering processes such as photo-oxidation. Here, we report the effects of leachates from UV-irradiated microplastics towards the chlorophyte Scenedesmus vacuolatus . The microplastics tested were derived from an additive-containing electronic waste (EW) and a computer keyboard (KB) as well as commercial virgin polymers with low additive content, including polyethylene (PE), polyethylene terephthalate (PET), polypropylene (PP), and polystyrene (PS). Whereas leachates from additive-containing EW and KB induced severe effects, the leachates from virgin PET, PP, and PS did not show substantial adverse effects in our autotrophic test system. Leachates from PE reduced algae biomass, cell growth, and photosynthetic activity. Experimental data were consistent with predicted effect concentrations based on the ionization-corrected liposome/water distribution ratios ( D lip/w ) of polymer degradation products of PE (mono- and dicarboxylic acids), indicating that leachates from weathering PE were mainly baseline toxic. This study provides insight into algae toxicity elicited by leachates from UV-weathered microplastics of different origin, complementing the current particle- vs. chemical-focused research towards the toxicity of plastics and their leachates. Graphical abstract